PARADIGMA PENDIDIKAN SISTEMIK-ORGANIK: Sebuah Upaya Inovatif Dalam Pendidikan - Djuwairiyah Djuwairiyah; Abd. Muqit (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
Education is a necessity of human life. The human educational process life of man, educated, acquired, trained, directed the school system. The education system in schools are expected to be able to make a man who has superior good kognitive, affective , and psychomotor . The maximum ability of student can be formd from an educational institution with systemic - organic paradigm, all components of education make an active role and every function apply and linkages cooperation with the otherÂ function.